The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/coatings12111735
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Modeling and Simulation Analysis of Inter-Shaft Bearings with Local Defects Considering Elasto-Hydrodynamic Lubrication

Abstract: As an important component of large engines, inter-shaft bearing is easily damaged due to its poor working conditions. By analyzing the time–frequency distribution rules of fault signals and the evolution law of micro-faults, the bearing failure mechanism can be revealed, and the bearing failure can be monitored in real time and prevented in advance. For the purpose of studying the mechanism of inter-shaft bearing faults, a 4-DOF (degree of freedom) dynamic model of inter-shaft bearing with local defects consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…According to the series-parallel relation of stiffness, total stiffness can be expressed as Equation (12).…”
Section: Calculation Of Stiffness and Dampingmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the series-parallel relation of stiffness, total stiffness can be expressed as Equation (12).…”
Section: Calculation Of Stiffness and Dampingmentioning
confidence: 99%
“…Subsequently, He et al 11 provided a technique to precisely and quantitatively assess the extent of local faults in bearings by examining the transient energy of fault pulses. Tian et al 12 used REB modelling methods to investigate the characteristic of inter-shaft bearing fault signals and the evolution of micro-faults. Liu et al 13 suggested a novel dynamic modelling approach for analysing REB contact and vibration characteristics during fault evolution.…”
Section: Introductionmentioning
confidence: 99%
“…It has been more than 50 years since vibration monitoring was proposed in China [12]. Due to the domestic economic and social construction needs, the total number of power unit assemblers is large and the application demand is great; thus, the domestic researchers have unique insights into the research of vibration monitoring fault diagnosis methods and fault mechanisms [13]. Although the start was lagging behind, after more than 50 years of practice in field fault diagnosis, we have accumulated rich knowledge and experience in unit vibration fault characteristics, and have produced long-term and in-depth research on the generation of these faults and the mechanism of generating vibration [14].…”
Section: Technology Development Historymentioning
confidence: 99%